Comparative Analysis of the Gut Microbiota of Three Sympatric Terrestrial Wild Bird Species Overwintering in Farmland Habitats - Lu, Zhiyuan; Li, Sisi; Wang, Min; Wang, Can; Meng, Derong; Liu, Jingze (Frontiers in Microbiology, 2022)
The gut microbiota of wild birds are affected by complex factors, and cross-species transmission may pose challenges for the host to maintain stable gut symbionts. Farmland habitats are environments strongly manipulated by humans, and the environmental characteristics within a large area are highly consistent. These features provide the ideal natural conditions for conducting cross-species comparative studies on gut microbiota among wild birds. This study aimed to investigate and compare the gut microbiota of three common farmland-dependent bird species, Great Bustard (Otis tarda dybowskii), Common Crane (Grus grus), and Common Coot (Fulica atra), in a homogeneous habitat during the wintering period. The results indicated that under the combined action of similar influencing factors, the gut microbiota of different host species did not undergo adaptive convergence, maintained relatively independent structures, and exhibited host-driven signals. In addition, we also detected various pathogenic genera that may cause outbreaks of periodic infections among sympatric migratory birds. We conclude that phylosymbiosis may occur between some wild birds and their gut microbiota. Usage of non-invasive methods to monitor the changes in the gut microbiota of wild bird fecal samples has important implications for the conservation of endangered species.